(untitled) (Research, Society and Development, 2021)
The Cerrado is the second largest biome in South America, occupying about 23% of the national territory, but which has been losing a large part of its native vegetation due to deforestation and anthropic fragmentation. This study aimed to understand the behavior of an area under restored in the biome, through the prognosis of the forest fragment using the class movement ratio method. Two forest inventories were carried out, in which all individuals with a CAP (circumference at chest height) greater than 15 cm were measured, for later adjustment of the nonlinear models of periodic increment, entry and mortality. Results showed individuals density loss of, indicating the phase transition from “construction” fragment to “degradation”. The main factors of degradation were accessibility to the site, disposal of urban waste and lack of planning for the restoration project, failing to take into account the principles of ecological succession and the survey of environmental reference information. However, the area showed regeneration capacity if the correct techniques are adopted that interfere with the restoration process, as there was an increase in the number of individuals in the smallest diameter class (2023) compared to previous years; increased growth in the penultimate class, followed by stabilization; reduction in the density loss of individuals, between the 2014-2017 and 2017-2023 intervals; and trend of the diametric distribution in “inverted J” in 2023.